Papua Land of Peace As a Humanitarian Program For Local People In Unitary State Republic of Indonesia - Wambrauw, Joram (Papua Law Journal, 2017)
This study aims for the actual problems in the field of politics, law and security in the context of Papua Land of Peace. This research is prescriptive legal research with normative juridical approach method in the form of research on the principle with data collection technique through literature study in the form of primary, secondary and tertiary legal material with qualitative analysis of legal materials. The results of the study show that Papua Land of Peace is a humanitarian program to protect the Papuan people who inhabit it, as well as to protect it as citizens of Indonesia in the NKRI container. Therefore it is necessary to be well and carefully identified various matters which are the factors causing the situation in which Papua will not become a Land of peace.